"Problem" directors and audit fees. Issue 1 (14th February 2019) - Habib, Ahsan; Bhuiyan, Md. Borhan Uddin; Rahman, Asheq
Abstract : This study investigates the association between audit fees and the presence of "problem" directors on corporate boards and audit committees. "Problem" directors, in this context, are those directors who have been involved in corporate financial failures and integrity indiscretions in the past. Auditors regard the presence of such directors on boards and audit committees as audit risk, and may have to enhance their audit procedures, leading to higher audit fees. Using a sample of 9, 175 firm‐year observations from 2004 to 2010 of US firms, we find that the presence of "problem" directors on boards and audit committees is associated with higher audit fees. This finding has a policy implication for corporate managers, that they should be mindful of the increase in perceived audit risk that arises from professional and personal attributes of directors when recruiting individuals to serve on their boards.